INTRODUCING FOREIGN EXPERIENCE INTO THE PRIMARY EDUCATION SYSTEM IN UZBEKISTAN AND ACHIEVEMENTS IN INTERNATIONAL COOPERATION - Furkat Kodirjon ugli Isokjanov (Journals Park Publishing, 2025)
Nowadays, the process of widespread integration of digital technologies into Uzbekistan’s education system is actively underway. The use of electronic textbooks, distance learning platforms, and modern technological tools in schools is bringing the educational process to a qualitatively new level.
Keywords: Finnish education system, PISA, PIRLS, innovative methods, interactive approach, scientific cooperation, modernization, Education Law, reforms, Strategy for the Development of the Education and Science System, national education policy.